ANALYSIS OF BULBOUS BOW RESISTANCE WITH DIMPLE (BASIN) ON KRI CLASS STRATEGIC SEALIFT VESSEL (SSV) USING CFD SOFTWARE - Dwi Putra Maulana; Irfan Syarif Arief; Cahya Kusuma; wawan kusdiana; Mohammad Syaifi (JOURNAL ASRO, 2020)
The function and role of the Strategic Sealift Vessel (SSV) ship type is very important. Modifications andchanges to improve the value of efficiency will be very necessary. This efficiency value is closely related to thevalue of Ship Resistance , where if the Resistance value goes down, the value of the ship's efficiency will rise.The increase in efficiency is then expected to reduce fuel consumption and increase speed. In several studies,ways have been improved to improve the condition, one of them is by adding a Dimple to the Surface Area ofthe ship, this modification will reduce the friction Resistance that the ship will receive by reducing the WettedSurface Area that the fluid will pass at certain speeds and conditions. . This modification will be applied to theship's Bulbous Bow section. In this way it is expected to improve the value of the Resistance produced by theBulbous Bow installed in the ship, without having to carry out significant changes or modifications and changethe shipbuilding of the existing Linesplane. Furthermore, the analysis is carried out by modeling using 2D and3D CAD Software and Model Experiments using CFD Applications. After carrying out the entire process ofRunning with the CFD Software to determine the value of the Ship Resistance . The final conclusion is in theform a reduction the value of vessel Total Resistance the Running Bow section of 31.53% in the 4th variationsand Fn used is 0,341.Keywords: Boulbous Bow, CFD, Dimple, Reduction, Resistance